Dynamic Traffic Assignment in a large-scale transport model (COMPASS): Udvidet resumé - Rasmussen, Thomas Kjær; Brun, Bjarke; Hansen, Christian Overgård (Proceedings from the Annual Transport Conference at Aalborg University, 2021)
A large-scale Dynamic Traffic Assignment (DTA) has been developed for a new activity-based traffic model for the Greater Copenhagen Area (Compass) to capture network dynamics that is not possible in static route choice models. The DTA model improves the estimate of peak hour travel times and provides similar or even better link load accuracy than the static route choice model.